Wind tunnel testing and frequency domain buffeting analysis of a 5000 m suspension bridge. Issue 7 (May 2021) - Xia, Jinlin; Li, Ke; Ge, Yaojun
Buffeting's importance is highlighted in the case of super-long bridges. It remains unclear how buffeting will perform and whether the traditional methods still apply when bridge's span is approaching its upper limitation. To figure out this, a full aeroelastic model testing has been carried out with the span arrangement 2000+5000+2000 m. A comparison with the existing bridges reveals the similarities and differences. It shows vertical and torsional buffetings are important for a 5000 m bridge while lateral response is almost static. Fundamental modes contribute most kinetic energy. With the increasing of wind speed, the aerodynamic coupling effect becomes prominent while the structural coupling effect keeps limited. Afterwards, four analytical methods, namely SRSS and CQC, with and without self-induced forces, are used for the buffeting displacements. The calculation indicates the multi-mode (CQC) analysis is still applicable on a 5000 m bridge but the mode-by-mode (SRSS) method is risky since the neglection of aerodynamic coupling effect. Parameter analysis shows aerodynamic admittance function and force coherence are decisive while the cross terms are of secondary importance. Since all data is experimentally measured, the reliability of analytical results can be ensured.